Facilitating employee excellence: A study on the mediating role of organizational virtuousness and individual creativity in Surabaya's finance company, Indonesia - Dutahatmaja, Angga; Kusmaningtyas, Amiartuti; Mujanah, Siti (Journal of Social Economics Research, 2025)
The purpose of this study is to investigate the impact of authentic leadership capabilities and managerial coaching skills on individual performance, taking into account organizational virtuousness and individual creativity as mediating variables among financial sector workers in Surabaya City, Indonesia. The sample of this study comprises 384 respondents from finance firms in Surabaya, collected through a survey distributed via Google Forms. The analysis employed Structural Equation Modeling (SEM) using Smart PLS to examine the data. The research findings indicate a positive and significant correlation between authentic leadership and employee performance within Surabaya's financial sector. Conversely, a manager's coaching skills do not have a significant impact on individual performance. Organizational virtuousness emerged as a mediator in the relationships between authentic leadership, managerial coaching skills, and individual performance, emphasizing its role in enhancing employee performance. Additionally, individual creativity acted as an intermediary in the relationship between managerial coaching skills and individual performance. Therefore, managerial recommendations include promoting authentic leaders who endorse ethical practices within the organization and encouraging innovative work among employees to improve overall performance standards.